Status Iddah Wanita yang Ditalak Setelah Melakukan Histerektomi dalam Perspektif Hukum Islam - Nailissa'adah, Nailissa'adah (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2015)
This study deals with Islam’s response to contemporary issues, particularly to address the issues of the ultrasound technology. The results of the research are: first, ultrasound is a diagnostic technique for testing the inner structure of the body that involves the formation of two-dimensional shadows with ultrasonic wave. The advantage of the ultrasound technique is that it can detect the presence of the fetus in the womb of a woman at the age of 5-7 weeks of pregnancy. In Islamic jurisprudence discourse, there are some opinions among the Muslim scholars who confirm the wisdom of ‘iddah (the waiting period) for woman that it is more dominant to a biological factor which wants to know the net of the womb. Whereas the ultrasound technique is able to determine or detect the woman’s uterus weather she is pregnant or not without having to wait up to three months or four months and ten days. Second, the ultrasound technique can detect fetus quickly and accurately. It cannot affect the provision of ‘iddah which is mentioned in al-Qur’an since bara’atur rahm is the wisdom of ‘iddah. On the other hands, the wisdom cannot be relied in forming law. In addition, the wisdom of determining ‘iddah is not only seen from one side but there are some things behind the regulation of ‘iddah. They are as a tribute to her husband who had died, giving an opportunity return for a man and a woman, as well as a way of worship in carrying out the command of Allah (ta'abbudi) which is ghair ma'qul alma'na (the law does not absolutely require a logic). [Penelitian ini bertujuan untuk menjawab beberapa persoalan mengenai status iddah wanita yang ditalak setelah melakukan histerektomi dalam perspektif hukum Islam. Penelitian ini menggunakan teknik pengumpulan data melalui teknik dokumentasi, dengan cara membaca dan menelaah buku-buku yang berkaitan dengan histerektomi sebagai penyebab berhentinya menstruasi. Kemudian, data yang terkumpul dianalisis menggunakan teknik deskriptif dan pola pikir induktif-deduktif. Hasil penelitian menyimpulkan bahwa terdapat tiga macam histerektomi yang menyebabkan berhentinya haid seorang wanita. Pertama, histerektomi total, adalah operasi pengangkatan rahim dan serviks, tanpa ovarium dan tuba fallopi. Kedua, histerektomi subtotal, adalah operasi pengangkatan rahim saja, dan ketiga histerektomi total dan salfingo-ooforektomi bilateral, adalah operasi pengangkatan rahim, serviks, ovarium dan tuba fallopi. Apabila haid seorang wanita berhenti, dan tertalak oleh suaminya, maka berimplikasi terhadap status iddahnya. Dalam analisis hukum Islam, wanita yang tertalak oleh suaminya dan sebelumnya pernah melakukan histerektomi, maka iddahnya selama tiga bulan. Apabila seorang wanita tengah menjalani iddah, kemudian melakukan histerektomi, maka iddahnya berubah dari iddah dengan menggunakan perhitungan quru' menjadi iddah dengan perhitungan bulan selama tiga bulan karena telah menopause.]